The rs4712527 Polymorphism in the CDKAL1 Gene: A protective factor for proliferative diabetic retinopathy progress in type 2 diabetes - Yang, Pablo (2018)
Purpose: Diabetic retinopathy (DR) is one of the chronic retinal disorders linked to diabetes and remains the leading cause of blindness in working-age people. Many studies have demonstrated the existence of associations between type 2 diabetes mellitus (T2DM) and variants in the cyclin-dependent kinase 5 regulatory subunit?associated protein 1-like 1 (CDKAL1) gene. Here, weperformed a case-control study in the CDKAL1 gene (rs4712527 polymorphism) to investigate the potential association between this single-nucleotide polymorphism (SNP) and DR risk. Methods: Two hundred thirty-one patients with T2DM (126 patients with proliferative diabetic retinopathy [PDR] and 105 patients without diabetic retinopathy [WDR]), who assisted at the CentroPrivado de Ojos Romagosa, Fundacio´n VER, were studied. An independent cohort of 98 patients (56 with PDR and 42 with WDR) from the Hospital Nacional de Clı´nicas was taken for replication. A complete ophthalmological examination included an externalexamination of the eye and adnexa, pupil responsiveness, and slit-lamp biomicroscopic examination. Genotyping of rs4712527 was carried out by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The odds ratio (OR) and 95% CI were calculated by unconditional logistic regression adjusted for diabetes duration, body mass index, insulin therapy,HbA1c, total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglycerides, and systolic and diastolic blood pressure. Results: Analysis from the rs4712527 SNP in the Centro Privado de Ojos Romagosa, Fundacio´n VER, cohort was found to be associated with decreased risk of PDR both before and after adjustment, under the codominant (adjustedOR ¼ 0.16 [95% CI, 0.06-0.44]; P ¼ 4e-04), dominant (adjusted OR ¼ 0.17 [95% CI, 0.07-0.43]; P ¼ 1e-04), overdominant (adjusted OR ¼ 0.20 [95% CI, 0.08-0.52]; P ¼ 5e-04), and log-additive (adjusted OR ¼ 0.28 [95% CI, 0.13-0.59]; P ¼ 4e-04)models. In the combined analysis including both cohorts, the rs4712527 was nominally involved as a protective factor in the development of DR. Conclusions: Our findings suggest that the rs4712527 in the CDKAL1 gene might be involved in the protection to develop PDR in T2DM.